Resilience theory constructs and psychotherapeutic practices with SGD individuals : a scoping review of psychological research literature - Martin, Jarred H. (University of Pretoria, 2025)
Mini Dissertation (MA (Clinical Psychology))--University of Pretoria, 2025.